Modified Limberg Flap for Pilonidal Sinus - Thapa, Prabin Bikram; Maharjan, DK; Ghimire, R; Shrestha, SK (Nepal Journal of Dermatology, Venereology & Leprology, 2017)
Background: Pilonidal sinus disease is a common condition usually seen in young adults. Although several methods of treatment have been described, but all have been associated with high recurrence rates. This study was carried out to evaluate the advantages and results of rhomboid excision and Limberg flap reconstruction in the management of pilonidal sinus disease. Objective: To evaluate the advantages and results of rhomboid excision and Limberg flap reconstruction in the management of pilonidal sinus disease Material and Methods: This was prospective descriptive study conducted in Unit III, Department of Surgery, Kathmandu Medical College Teaching Hospital from August 2013 to August 2015. First 50 patients with diagnosis of pilonidal sinus were included .Exclusion criteria was patients with pilonidal abscess. Results: Total 50 patient were included in 2 years time. Mean age was 23.48 ± 3.9 years with all male patients only. Median duration of surgery was 32 ± 4.4 minutes .Median time for normal activities was 21± 3.9 days and median follow up time was 18±8.5 months. No recurrence was noted till then. Post surgery, patient applied hair removal cream: 44%, hair shaving: 34% and laser therapy for hair follicles: 22%. Conclusion: Modified Limberg flap is better option for pilonidal sinus with least recurrence. However, post surgical counseling for hair removal is very important in order to prevent recurrence and should be multidisciplinary approach along with dermatologist colleagues.